PENGARUH GAYA KEPEMIMPINAN DAN SARANA PRASARANA TERHADAP KINERJA MELALUI MOTIVASI PADA BAGIAN PENGADAAN BARANG DAN JASA KOTA PROBOLINGGO - Ahmad Munif (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
The aim of this research is to test and analyze the influence of leadership style and infrastructure on performance through motivation in the Probolinggo City Goods and Services Procurement Section. This type of research is descriptive and verification analysis research with data analysis using the Smart PLS 3.0 application. The sampling technique used the simple proportional sampling method with a population and sample size as large as the total population of the Probolinggo City Goods and Services Procurement Section, totaling 37 people. The results of the research show that leadership style has no influence on motivation in the Goods and Services Procurement Section of the city of Probolinggo. Leadership style has an influence on performance in the Goods and Services Procurement Section of the city of Probolinggo. Infrastructure and infrastructure have an influence on motivation in the Goods and Services Procurement Section of the city of Probolinggo. Infrastructure has no influence on the performance of the Probolinggo City Goods and Services Procurement Section. Motivation has no influence on performance in the Probolinggo City Goods and Services Procurement Section. Leadership style has no influence on performance through motivation in the Goods and Services Procurement Section of the city of Probolinggo. Infrastructure has no influence on performance through motivation in the Goods and Services Procurement Section of the city of Probolinggo.